NEW MATERIAL ON THE HYAENODONTIDAE (MAMMALIA, CREODONTA) FROM THE ERGILIYN DZO FORMATION (LATE EOCENE OF MONGOLIA) AND SOME NOTES ON THE SYSTEM OF THE HYAENODONTIDAE - Lavrov A.V. (My University, 1999)
Remains of Macropterodon zelenovi, gen. et sp. nov. a very large representative of Hyaenodontinae (the size of Hyainailouros), and of a representative of the Proviverrinae gen. et sp. indet., (the size of Dissopsalis and represented by an isolated m3), are described from the Ergiliyn Dzo Formation of the Khoer Dzan Locality (Late Eocene, Mongolia). Macropterodon is characterized by a massive p4 and a very large ml, usually reduced in large Hyaenodontinae. The new finds from the Ergiliyn Dzo Formation deposits provide new evidence to the previously discovered biological diversity maximum of the Hyaenodontinae and Proviverrinae during the Late Eocene in Asia. The following composition of the Hyaenodontidae is adopted: the tribe Apterodontini (composed ofApterodon and newly described Quasiapterodon), the tribe Hyaenodontini, and distinct genera that cannot be included in the tribes. The amended list of Hyaenodontidae from the Ergiliyn Dzo Formation now comprises: Neohyaenodon gigas, N. insertus, Hyaenodon eminus, H. mongolensis (originally described as Megalopterodon mongolensis Dashzeveg, 1964), Macropterodon zelenovi gen. et sp. nov., "Pterodon" exploratus (Dashzeveg, 1985), Proviverrinae gen. et sp. indet.
Keywords: Eocene; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен